Fibroblast activation protein‐α, a stromal cell surface protease, shapes key features of cancer associated fibroblasts through proteome and degradome alterations. Issue 1 (11th August 2015) - Koczorowska, M.M.; Tholen, S.; Bucher, F.; Lutz, L.; Kizhakkedathu, J.N.; De Wever, O.; Wellner, U.F.; Biniossek, M.L.; Stahl, A.; Lassmann, S.; Schilling, O.
Abstract : Cancer associated fibroblasts (CAFs) constitute an abundant stromal component of most solid tumors. Fibroblast activation protein (FAP) α is a cell surface protease that is expressed by CAFs. We corroborate this expression profile by immunohistochemical analysis of colorectal cancer specimens. To better understand the tumor‐contextual role of FAPα, we investigate how FAPα shapes functional and proteomic features of CAFs using loss‐ and gain‐of function cellular model systems. FAPα activity has a strong impact on the secreted CAF proteome ("secretome"), including reduced levels of anti‐angiogenic factors, elevated levels of transforming growth factor (TGF) β, and an impact on matrix processing enzymes. Functionally, FAPα mildly induces sprout formation by human umbilical vein endothelial cells. Moreover, loss of FAPα leads to a more epithelial cellular phenotype and this effect was rescued by exogenous application of TGFβ. In collagen contraction assays, FAPα induced a more contractile cellular phenotype. To characterize the proteolytic profile of FAPα, we investigated its specificity with proteome‐derived peptide libraries and corroborated its preference for cleavage carboxy‐terminal to proline residues. By "terminal amine labeling of substrates" (TAILS) we explored FAPα‐dependent cleavage events. Although FAPα acts predominantly as an amino‐dipeptidase, putative FAPα cleavage sites in collagens are present throughout the entire protein length. In contrast, putative FAPα cleavage sites in non‐collagenous proteins cluster at the amino‐terminus. The degradomic study highlights cell‐contextual proteolysis by FAPα with distinct positional profiles. Generally, our findings link FAPα to key aspects of CAF biology and attribute an important role in tumor–stroma interaction to FAPα. Highlights: We investigated the secretome and degradome of CAFs with FAPα loss‐ and gain‐of‐function. FAPα controls levels of secreted proteins linked to TGFβ signaling, angiogenesis and matrix remodeling. Functional studies substantiate a role of FAPα in TGFβ signaling, angiogenesis and matrix remodeling. We corroborated the specificity of FAPα for P1 proline using proteome‐derived peptide libraries. First FAPα substrate candidates were identified.